A participação popular como espaço de experiência e a democracia como horizonte de expectativa: análise dos projetos políticos na Constituinte de 1987-1988 - Braga, Julio Trevisam (2021)
In the midst of the whole context of redemocratization that Brazil experienced, from the 1970s onwards, as a result of wear and resistance to the atrocities protected by the Institutional Acts of the 1964 civil-military dictatorship, a new political culture took shape and popular demands for a effective democracy and effective participation practices were increasingly present in the country. However, the opening of the 1987- 1988 National Constituent Assembly ended up bringing together different projects of democracy and participation, the main ones being analyzed, the conservative, the liberal and the left. On the other hand, social movements were organizing themselves to demand that the new Constitution meet their demands. Thus, based on an approach capable of confronting historical vestiges with the current debate around the object, this research aims to understand the formation of this political culture, confronting the different projects of democracy and participation originating from the three distinguished ideological spectra, namely, conservative groups, liberals and leftist progressives, as well as measuring the intensity of popular participation both among social movements and among the population not linked to these movements. In this sense, appropriating the conceptual repertoire of Reinhart Koselleck (space of experience/horizon of expectation) and E. P. Thompson (experience/consciousness), which seeks to define how this political culture is precisely the debate and the confrontations that will be constituted around the construction of a Constitution that was able, in the end, to compose the fabric of a new democracy, highlighting the different projects in conflict